Working in residential homes for elderly people - Brearley, C. Paul (Place of publication not identified : ROUTLEDGE, 2023)
First published in 1990, Working in Residential Homes for Elderly People outlines the purposes and objectives of residential homes and what it is like to live and work in them. The author looks at the factors that make for a good quality of life, considering how these can be promoted and how staff can work with people, both individually and in groups, to help them get the best out of life. He reviews prevalent thinking about what happens to people as they grow older, and, at a practical level, he looks carefully at the day-to-day management of homes, suggesting how they should be organized in order to get the best out of the staff, buildings and resources. Unique in its coverage of the process of ageing, good practice, and good management, the book takes into account the differing needs of both residents and staff. With its emphasis on the various aspects of the flexible, individual support necessary in providing a good home', it will be invaluable to social work and social care students, residential workers, and their managers.
OCLC-licensed vendor bibliographic record.
Keywords: Old age homes -- United States -- Management; Older people -- Institutional care -- United States; Social work with older people -- United States; Social service